ANOTHER PINK-SPORED AND BROWN-STALKED SPECIES OF STACHYBOTRYS - Mien A Rifai (BRIN Publishing (Penerbit BRIN), 1974)
The new species Stachybotrys palmijunci Rifai is described and illustrated based on a collection on a decaying stem of the rattan Daemonorhops melanochaetes from West Java. It is compared with the closely related Javanese species Stachybotrys bambusicola Rifai.